Intravitreal safety profiles of sol-gel mesoporous silica microparticles and the degradation product (Si(OH)4) - Yaoyao Sun; Kristyn Huffman; William R. Freeman; Michael J. Sailor; Lingyun Cheng (Taylor & Francis Group, 2020)
Mesoporous silica has attracted significant attention in the drug delivery area; however, impurities can be a source of toxicity. The current study used commercial microparticles produced at large scale in a well-controlled environment. Micrometer sized mesoporous silica particles were acquired through a commercial vendor and pore structures were characterized by SEM. The three silica particle formulations had a diameter of 15 micrometers and three different pore sizes of 10 nm, 30 nm, and 100 nm. The fourth formulation had particle size of 20-40 micrometers with 50 nm pores. Before in vivo tests, an in vitro cytotoxicity test was conducted with silicic acid, derived from the sol-gel particles, on EA.hy926 cells. Low concentration (2.5 µg/mL) of silicic acid showed no cytotoxicity; however, high concentration (25 µg/mL) was cytotoxic. In vivo intravitreal injection demonstrated that 15 um silica particles with 10 nm pore were safe in both rabbit and guinea pig eyes and the particles lasted in the vitreous for longer than two months. Formulations of with larger pores demonstrated variable localized vitreous cloudiness around the sol-gel particle depot and mild inflammatory cells in the aqueous humor. The incidence of reaction trended higher with larger pores (10 nm: 0%, 30 nm: 29%, 50 nm: 71%, 100 nm: 100%, p < .0001, Cochran Armitage Trend Test). Sol-gel mesoporous silica particles have uniform particle sizes and well-defined pores, which is an advantage for implantation via a fine needle. Selected formulations may be used as an intraocular drug delivery system with proper loading and encapsulation.